THE RELATIONSHIP BETWEEN MENTAL FATIGUE AND LEARNING MOTIVATION OF GUIDANCE AND COUNSELING STUDENTS IN THE DIGITAL ERA: A MULTI-SITE STUDY ACROSS HIGHER EDUCATION INSTITUTIONS - Abid Raisardhi; Nasution, Salsabila (Jurnal Kopendik, 2026)
This study aimed to examine the relationship between mental fatigue and learning motivation among Guidance and Counseling (GC) students in the digital era. Mental fatigue has emerged as a critical challenge in technology-based learning environments, potentially undermining both intrinsic and extrinsic academic motivation. This study employed a quantitative correlational approach involving 803 GC students from multiple higher education institutions across Indonesia, selected through purposive sampling. Data were collected using two validated psychological scales: the Mental Fatigue Scale and the Learning Motivation Scale. Spearman’s rank correlation was adopted as a conservative analytical approach; while Q-Q plots indicated approximately normal distributions, the Shapiro-Wilk test yielded p < .001 at N = 803, and Spearman was selected as a conservative response to the test’s known sensitivity with large samples. Results revealed a significant negative relationship between mental fatigue and learning motivation (ρ = -0.323, p < .001, 95% CI [-0.384, -0.260]), indicating that higher levels of mental fatigue are associated with lower learning motivation. These findings highlight the urgency of digital-based guidance and counseling interventions to effectively manage students’ mental fatigue and promote sustainable learning motivation.